Características agronômicas, adaptabilidade e estabilidade produtiva de genótipos de feijão caupi de porte semi-ereto no estado de Roraima - Arruda, Katherine Rodrigues de (2011)
Trials have been conducted to evaluate 17 semi erect cowpea genotypes in the years 2007, 2008 and 2009, in the period from July to September of each year aiming identify those with wide adaptability and stability of production in Roraima State. The experimental design was a randomized complete block design with 17 treatments (genotypes) and four replications. The collected data were the number of days elapsed from plant emergence until the beginning of flowering, lodging, length of five pods, mass of five pods, number of grains of five pods, grains weight of five pods and grains weight in each plot, corrected to standard moisture of 13% and transformed to productivity (kg ha-1). Based on data colected were stimated weight of 100 grains and grain index. The results were submitted to individual and jointly analysis of variance and were later carried out the analysis of adaptability and stability of production by the methodologies proposed by Eberhart and Russel (1966) and Annicchiarico (1992). The best genotypes were BRS Cauamé, BRS Tumucumaque and BRS Guariba cultivars. No experimental lines overcame these three cultivars when considering all variables evaluated.